Dialogismo e igualdad sexual en la autobiografía de John Stuart Mill - Nocera, Pablo (Nómadas. Critical Journal of Social and Juridical Science, 2009)
The life of John Stuart Mill took place in the Victorian era and it is portrayed in his autobiography as the development of a mind in a knowledge acquisition process. Although this narrow point of view could detract some interest among the works that distinguish the genre, his assessments deserve a careful approach. Therefore, the paper analyses his autobiography in the wider English context that allows understanding his roots in the spiritual autobiography subgenre, especially those of the XVII century. Second, the paper analyses the links that Mill’s autobiography shares with Victorian naturalist-rationalist signs, to focus, after that, his original and specific contribution in three dimensions. Firstly, the dialogic level in which Mill organizes his exposition, where his own voice lives with the masculine father’s voice and the female future wife’s voice, Harriet. Second, the analysis focuses the way in which Mill rewrites the subjection to the father’s voice into an equality relationship with the female voice, so he demolishes the sexual differences in biological sense. Finally, the last one describes the way in which his autobiography presents the Victorian structure of feeling changes in the perceptions about sexual equality and the public dimension of the autobiographical voice.
Keywords: Autobiographical genre; Dialogism; Sexual equality; Spiritual autobiography; Victorian era; John Stuart Mill